Impact of Maintenance Methods of an Overgrown Lowland River on its Hydraulic Conditions - Wolski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of numerical analyses carried out in the IRIC environment on the Nays2DH hydrodynamic model regarding the impact of plants in the riverbed and watercourse maintenance on hydraulic conditions. The research material was collected for the actual input variant in October 2018 on the Ślęza River in Wrocław.
Keywords: river; lowland river; vegetation; ecohydrology; overgrowning river; nature-based clearning; rzeka; rzeka nizinna; ekohydrologia; oczyszczanie